Providing Rehabilitation to Narcotics Abuse Victims Who Voluntarily Surrender to the National Narcotics Agency of North Sumatra Province - Aisyah Lubis; Joice Saveris Pandiangan; Rikki Juniansen Simarmata; Dewi Ervina Suryani (International Journal Reglement & Society (IJRS), 2022)
Rehabilitation is the stage of healing for those who have a dependence on narcotics to be able to return to a healthy life physically and spiritually. In the ACT No. 35 Year 2009 On Narcotics in article 54 is described that addicts or victims of abuse of narcotic required to undergo medical rehabilitation and social rehabilitation. The National Narcotics agency is a Non-ministerial Government Agencies (LPNK) who have duties in the prevention, combating abuse, and trafficking of psychotropic substances. The National Narcotics agency chaired by the Head of the President, the National Narcotics Agency has the authority provided for in article 71 of LAW No.. 35 Year 2009, that the Narcotics Agency has the authority in providing rehabilitation to the victims and must be executed. Before the survivors undergoing rehabilitation phase, then the victim will undergo a stage of the assessment according to the SOP is different, in this stage of the victims can be divided into 2, for victims who give themselves or caught red-handed by the National Narcotics Agency then the SOUP run for the victim is the Assessment of the Voluntary, however, if the victim is caught red-handed by the Police, then the SOP that will be run victim is Assessment Compulsary.